Electronic and Magnetic Anisotropies in FeSe Family of Iron-Based Superconductors - Chen, Tong; Yi, Ming; Dai, Pengcheng (Frontiers in Physics, 2020)
Most parent compounds of iron-based superconductors (FeSCs) exhibit a tetragonal-to-orthorhombic lattice distortion below Ts associated with an electronic nematic phase that breaks the four-fold (C4) rotational symmetry of the underlying lattice, and then forms collinear antiferromagnetic (AF) below TN (TN ≤ Ts). Optimal superconductivity emerges upon suppression of the nematic and AF phases. FeSe, which also exhibits a nematic phase transition below Ts but becomes superconducting in the nematic phase without AF order, provides a unique platform to study the interplay amongst the nematic phase, AF order, and superconductivity. In this review, we focus on the experiments done on uniaxial pressure detwinned single crystals of FeSe and other FeSCs and highlight the importance of understanding the electronic and magnetic anisotropy in elucidating the nature of unconventional superconductivity.